Real-Time Health Care Monitoring System using IoT - Saminathan, Sasippriya; Geetha, K (International Journal of Engineering and Technology, 2018)
Incorporation of Information and Communication Technology (ICT) in healthcare industry explored the possibilities to optimize the supply of all the available medical resources and provide reliable, efficient healthcare services to the aged people and patients with physical disabilities and chronic illness. In consumer electronics and growing costs of healthcare a vision of connected e-health has evolved which constitute Personal Health Devices (PHD). Present day mobile devices are capable enough to gather data from various sensors and often play a role in physical fitness gateway and then data are collected in PHDs. The network overhead and suitability of the proposed solution for the different environment is presented which includes the integration of different wireless interfaces with cloud services. The work focuses on adapting the MQTT (Message Queue Telemetry Transport) communication model. This protocol is preferred over CoAP which is one-one protocol because it is one of the lightweight protocols used in TCP/IP and it has the feature of many to many communication models. The evaluation of the work is on a PHD prototype device and feasibility of the solution is discussed. The proposed work is to design and develop a Real-time healthcare monitoring system using IoT which is featured with Random Forest algorithm for heart disease prediction by gathering patient’s data from various PHD sensors and timely alert the caretaker as well as a doctor by sending messages through MQTT. It monitors the patient’s physiological parameters remotely and diagnoses the heart diseases as early as possible.The main motto is to reduce the cost of healthcare and give people the awareness about health and fitness.